THE EFFECT OF INDUSTRIAL VALUE ADDED, ENERGY CONSUMPTION, FOOD CROP PRODUCTION, AND AIR TEMPERATURE ON GREENHOUSE GAS EMISSIONS IN INDONESIA: A TIME SERIES ANALYSIS APPROACH - Swardanasuta, I Bagus Putu; Sandy, Nicholas Rahardian Kurnia; Rohmah, Nur Amaliyatur; Arindah, Yuli; Kartiasih, Fitri (Fakultas Pertanian, Universitas Janabadra, 2024)
Air quality and global warming, which cause climate change and affect many aspects of human life, have become important topics in recent years. The objective of this study is to assess the influence of greenhouse gas emissions on industrial added value, energy consumption, food crop production, and air temperature in Indonesia. The period covered is 1990–2022. The Granger causality test and the vector error correction model are employed to establish the causal connection between the variables, and the unit root test is used to confirm the data’s stationarity. The study’s findings demonstrate that, over the long run, greenhouse gas emissions in Indonesia are known to be positively impacted by energy use, crop output, and temperature. Short-term analysis shows that air temperature has a negative impact on greenhouse gas emissions in Indonesia, but the added value of industry, energy consumption, and food crop output have a favorable impact. In light of the study’s findings, it is anticipated to serve as the foundation for the Indonesian government’s deliberations when implementing the required policies to lower greenhouse gas emissions, while still paying attention to the added value in the industrial sector as well as a basis for determining other policies. In addition, controlling fossil energy consumption must also be actively carried out by intensifying the use of renewable fuels. Keywords: Greenhouse gases, Industrial value added, Energy consumption, Food crop production, Air temperature, VECM